Towards quadruple therapy for heart failure with reduced ejection fraction: DAPA-HF secondary analysis data - Zh. D. Kobalava; V. V. Medovchshikov; N. B. Yeshniyazov (Российский кардиологический журнал)
Patients with heart failure with reduced ejection fraction (HFrEF), despite optimal evidence-based treatment, have a high residual risk of adverse outcomes. The favorable results of studies on cardiovascular safety and the effectiveness of sodium-glucose cotransporter 2 (SGLT2) inhibitors in patients with type 2 diabetes (T2D), including outcomes associated with heart failure, were the reason for studying the effectiveness in patients with HFrEF regardless of the T2D status. For the first time in the DAPA-HF study, the SGLT2 inhibitor dapagliflozin in patients with HFrEF showed a positive effect on hard endpoints. Data of the secondary analysis confirmed the effectiveness of dapagliflozin regardless of the T2D status, therapy, age, and quality of life. The results of DAPA-HF have become a serious statement for changing the standards of the guideline-recommended therapy of HFrEF.